2021
DOI: 10.1371/journal.pone.0261032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact of commonly used medications on the oral microbiome of individuals living without major chronic conditions

Abstract: Background Commonly used medications produce changes in the gut microbiota, however, the impact of these medications on the composition of the oral microbiota is understudied. Methods Saliva samples were obtained from 846 females and 368 males aged 35–69 years from a Canadian population cohort, the Atlantic Partnership for Tomorrow’s Health (PATH). Samples were analyzed by 16S rRNA gene sequencing and differences in microbial community compositions between nonusers, single-, and multi-drug users as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Further analysis in these studies demonstrated that in addition to age, the following covariates contributed significantly to microbial variation: dentate, tobacco use, active caries, periodontal status and, gender/sex, whereas BMI and medication used failed to show a significant association with variation. Similarly, our team has previously shown minimal variation due to medication use within the Atlantic PATH cohort 38 , and only small associations between BMI and select beta diversity measures 28 . Tobacco use (Table 1 ) was very rare (3%) in the current cohort and included in the adjusted models.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Further analysis in these studies demonstrated that in addition to age, the following covariates contributed significantly to microbial variation: dentate, tobacco use, active caries, periodontal status and, gender/sex, whereas BMI and medication used failed to show a significant association with variation. Similarly, our team has previously shown minimal variation due to medication use within the Atlantic PATH cohort 38 , and only small associations between BMI and select beta diversity measures 28 . Tobacco use (Table 1 ) was very rare (3%) in the current cohort and included in the adjusted models.…”
Section: Discussionmentioning
confidence: 70%
“…This is a large population cohort (age 30–74 years) in the Atlantic region of Canada which includes detailed questionnaire data, biological samples, and clinical measures 34 , 35 . A portion of participants also have FI data 36 and 16S rRNA amplicon sequencing data from saliva samples 28 , 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis in these studies demonstrated that in addition to age, the following covariates contributed signi cantly to microbial variation: dentate, tobacco use, active caries, periodontal status and, gender/sex, whereas BMI and medication used failed to show a signi cant association with variation. Similarly, our team has previously shown minimal variation due to medication use within the Atlantic PATH cohort 41 , and only small associations between BMI and select beta diversity measures 28 . Tobacco use (Table 1) was very rare (3%) in the current cohort and included in the adjusted models.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, drugs used by the patients in order to control the different diseases may also influence the microbial composition and the diagnosis of periodontal disease, although research on medication use on the oral microbiome is limited. Thus, DeClercq and colleagues recently reported negligible effects of commonly used medications on microbial diversity and small differences in the relative abundance of specific taxa, suggesting minimal effect of commonly used medication on the salivary microbiome ( DeClercq et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%